Parameters of hydrogen plasma streams in QSPA-M and their dependence on external magnetic field - Ladygina, M.S.; Petrov, Yu.V.; Yeliseev, D.V.; Makhlai, V.A.; Kulik, N.V.; Staltsov, V.V. (Вопросы атомной науки и техники, 2021)
Present experimental studies are aimed at analysis of hydrogen plasma stream parameters in various working regimes of QSPA-M operation. Temporal distributions of plasma electron density are reconstructed with optical emission spectroscopy. The magnetic field influence on plasma streams parameters is analyzed. It is shown that in regimes with additional magnetic field the plasma electron density increases by an order of magnitude in comparison with a density value without magnetic field. The plasma velocity and energy density parameters as well as their temporal behaviors were estimatedin different operating regimes of QSPA-M facility. Features of plasma visible radiation were analyzed. This information is important for QSPA-M applications in experiments on interaction of powerful plasma streams with material surfaces. Проведені експериментальні дослідження спрямовані на аналіз параметрів водневої плазми у вільному потоці для різних робочих режимів роботи КСПП-M. За допомогою оптичної емісійної спектроскопії реконструйовано часові розподіли електронної густини плазми. Проаналізовано вплив магнітного поля на параметри плазмових потоків та показано, що густина плазми при роботі з додатковим магнітним полем зростає на порядок величини в порівнянні з густиною, виміряною без магнітного поля. Оцінено параметри швидкості та густини енергії плазми, а також їх поведінку під час розряду в різних режимах роботи установки КСПП-М. Проаналізовано особливості випромінювання плазми. Ця інформація дуже важлива для застосування КСПП-М у експериментах по взаємодії потужних плазмових потоків з поверхнями матеріалів. Проведенные экспериментальные исследования направлены на анализ параметров водородной плазмы в свободном потоке для различных рабочих режимов работы КСПУ-М. С помощью оптической эмиссионной спектроскопии восстановлены временные распределения плазменной электронной плотности. Проанализировано влияние магнитного поля на параметры плазменных потоков, и показано, что плотность при работе в дополнительном магнитном поле возрастает на порядок величины по сравнению с плотностью, измеренной без магнитного поля. Оценены параметры скорости и густоты энергии плазмы, а также их временное поведение в различных режимах работы установки КСПУ-М. Проанализированы особенности излучения плазмы. Данная информация очень важна для применения КСПУ-M в экспериментах по взаимодействию мощных плазменных потоков с поверхностями материалов.